Indonesia’s Image from China’s Perspective on South China Sea Dispute (A Preliminary Study on China’s Perception on Indonesia) - Kartikasari, Ardina (UI Scholars Hub, 2019)
This paper discusses the image of Indonesia in the eyes of China on the South China Sea (SCS) dispute. China circulated the map of Nine-dotted lines in 1993 and since then China has behaved ambiguously towards Indonesia as the dotted lines encompasses some part of Indonesia’s North Natuna waters. China insists two countries have overlapping interests over some of Indonesia’s Natuna Exclusive Economic Zone which China claims as it traditional fishing ground. China, however recognizes Indonesia’s sovereignty over the Natuna Islands and has been cautious when dealing with Indonesia on the Natuna issue. This behavior continues until the last three incidents occurred in Natuna waters in 2016. Although there are many studies on the South China Sea dispute and China’s policy towards Indonesia, few if any of them discuss specifically on China’s perspective towards Indonesia. Adopting image theory as an analytical framework, this paper figures Indonesia’s image on the eyes of China, which then shaped China’s perception toward Indonesia on SCS dispute. The main argument in this paper is China captures Indonesia’s image as an ally image. In this image, Indonesia is seen as an actor who can work together, has similar capabilities and cultural dimensions with China.